Structures, morphological control, and antibacterial performance of tungsten oxide thin films - Tan, Guang-Lei (2021)
The present work describes structural, morphological, and antibacterial properties of thin film coatings based on tungsten oxide material on stainless-steel substrates. Thin films were prepared by RF magnetron sputtering of W targets in the oxygen/argon plasma environment in 60 W sputtering power. The characterization of the specimens was made on the basis of microstructure and antibacterial properties of the thin films surface. The effect of O2/Ar ratio on the structure, morphology, and antibacterial properties of the tungsten oxide thin films was studied. Methods such as X-ray diffraction (XRD), scanning electron microscope (SEM), and Fourier Transform Infrared Spectroscopy (FTIR) were used to assess the properties of deposited thin films. XRD peak analysis indicates (100) and (200) of WO3 phase with hexagonal structure. Moreover, the micro-strain, grain size, and dislocation density were obtained. It is noteworthy that by increasing the oxygen percentage from 10% to 20%, the grain size decreases from 81 to 23 nm while the film micro-strain and dislocation density increases. The SEM results illustrates that tungsten oxide thin films are made of interconnected nano-points in a chain shape with sphere-shaped grains with diameter variation from 10 to 100 nm. The FTIR spectra displays four distinct bands corresponds to O–W–O bending modes of vibrations and W–O–W stretching modes of the WO3 films. The antibacterial effects of tungsten oxide thin films on steel stainless substrate against Escherichia coli bacteria are also examined for the first time and our observation shows that the number of bacteria on all tungsten oxide samples decreases after 24 h. The samples exhibit an excellent antibacterial performance. This paper renders a strategy through which the tungsten oxide thin films for antibacterial purpose and proposes that WO3 thin films are ideal for various medical applications including stainless steel medical tools, optical coatings, and antibacterial coatings.